Hair follicle-derived melanocyte transplant as a promising treatment strategy for vitiligo - Ruirui Fan; Jie Gao; Jin Chen (Stem Cell Research & Therapy)
Abstract Background The global incidence of vitiligo has been increasing in recent years, imposing psychological distress and social pressure owing to its refractory and recurrent nature. Traditional therapies often yield unsatisfactory outcomes, necessitating the development of new, effective therapies for vitiligo. In this study, we aimed to evaluate whether transplantation of hair follicle-derived melanocytes can restore pigmentation in depigmented skin associated with vitiligo. Methods We developed a method to isolate and culture hair follicle-derived melanocytes. We identified melanocytes at the cellular, protein, and gene levels and established a mouse model of vitiligo using the melanoma/T regulatory cell exhaustion induction method. We used a WOOD’s UV lamp, hematoxylin and eosin staining, immunohistochemistry, immunofluorescence, L-DOPA staining, Ferrous sulfate staining, and transmission electron microscopy (TEM) to characterize the vitiligo mouse model. Subsequently, we transplanted hair follicle-derived melanocytes into the mouse model using dermabrasion. Finally, the aforementioned methods determine whether hair follicle-derived melanocytes could survive and recolor vitiligo skin after transplantation. Results We successfully developed a method for isolating and culturing hair follicle-derived melanocytes. Immunofluorescence and flow cytometry results indicated that the cells expressed pigmentation markers such as tyrosinase, tyrosinase-related protein 1, and microphthalmia-associated transcription factor. L-DOPA staining revealed that there was some melanin in the melanocytes, confirming that the melanocytes were functional. Moreover, we successfully established a vitiligo mouse model that recapitulates the key clinical features of vitiligo, including epidermal depigmentation, CD8+/CD4 + T cell infiltration in the skin, and melanocyte loss, confirming that the mouse model reliably mimics human vitiligo. Moreover, vitiligo-afflicted skin was effectively recovered by transplantation of hair follicle-derived melanocytes. Notably, the skin color of the experimental group was similar to that of the control group. Immunofluorescence staining and immunohistochemistry results indicated the presence of melanocytes in the skin of the experimental group, while TEM confirmed that the melanocytes were functional after transplantation. Conclusion Transplantation of hair follicle-derived melanocytes may serve as a more effective therapeutic strategy for vitiligo than currently available methods.